Analisis Pengaruh Tingkat Kemiskinan, Tingkat Pengangguran Terbuka, Dan Indeks Pembangunan Manusia terhadap Pertumbuhan Ekonomi Provinsi Jawa Timur - Alvy Kusumawati; Wiwin Priana Primandhana; Muhammad Wahed (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
Economic growth is a main standard to measure the triumph of a development that has been achieved, as well as to determine where the development intends in the future. Economic growth explains the degree to which economic activities aim to realize people's income at particular times. The aim of this study is to analyze how much the effect of poverty level, open unemployment rate, and Human Development Index (HDI) on economic growth in East Java. The research used secondary data obtained from the Central Statistics Agency of East Java with per semester in 2008-2019. The analytical method used is Multiple Linear Regression Analysis with use Ordinary Least Square (OLS) model with SPSS (Statistic Program For Social Science) Version 13.0 program to indicate the effect of independent variables to dependent variables. The obtained result showed that poverty level and Human Development Index (HDI) have a significant positive effect on the economic growth in East Java. Variable open unemployment rate have a significant negative effect on the economic growth in East Java.